1992
DOI: 10.1111/j.1365-2052.1992.tb00142.x
|View full text |Cite
|
Sign up to set email alerts
|

Demonstration of serum albumin (ALB) polymorphism in wild rabbits, Oryctolagus cuniculus, by means of isoelectric focusing

Abstract: Genetic polymorphism of serum albumin was demonstrated by isoelectric focusing in wild rabbit populations from Portugal and England. Gene frequencies were estimated to be (1)ALB.I = 0-47, ALB*2 = 0*49,ALB*3 = 0.04, in Portugal, and (2) ALB*l = 0-60 and ALB*2 = 0-40, in England. One hundred Portuguese domestic rabbits of mixed breeds were all of ALB I type.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

1993
1993
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(2 citation statements)
references
References 7 publications
0
2
0
Order By: Relevance
“…This is clearly visible in some molecular markers like albumin (Ferrand and Rocha 1992) or carbonic anhydrase II (Branco and Ferrand 2003, unpublished results), as well as in some immunoglobulin allotypes (van der Loo 1987). UK rabbits were subsequently used as a source for the introductions that happened later in Australia and New Zealand, and the genetic analyses of those populations do confirm this hypothesis (Zenger et al 2003;Ferrand and Branco 2007).…”
Section: What Can We Infer About the Geographical Expansion Of The Ramentioning
confidence: 86%
“…This is clearly visible in some molecular markers like albumin (Ferrand and Rocha 1992) or carbonic anhydrase II (Branco and Ferrand 2003, unpublished results), as well as in some immunoglobulin allotypes (van der Loo 1987). UK rabbits were subsequently used as a source for the introductions that happened later in Australia and New Zealand, and the genetic analyses of those populations do confirm this hypothesis (Zenger et al 2003;Ferrand and Branco 2007).…”
Section: What Can We Infer About the Geographical Expansion Of The Ramentioning
confidence: 86%
“…Each of the homozygous ALB variants shows four fractions, two major bands and two minor more anodal bands, while after starch gel electrophoresis one strong cathodic and one weak anodic band were observed (Tucker 1968). It can be concluded that IEF is also useful for the demonstration of albumin variants in sheep as it was already shown for those in cattle, horses (Erhardt 1991b) and rabbits (Ferrand & Rocha 1992).…”
mentioning
confidence: 63%